1995
DOI: 10.1074/jbc.270.36.21226
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Fidelity of Translesion Synthesis of Site-specific N-2-Acetylaminofluorene Adducts during DNA Replication in a Human Cell Extract

Abstract: We have previously analyzed the effects of site-specific N-2-acetylaminofluorene (AAF) adducts on the efficiency and frameshift fidelity of SV40-based DNA replication in a human cell extract (Thomas, D. C., Veaute, X., Kunkel, T. A., and Fuchs, R. P. P. (1994) Proc. Natl. Acad. Sci. U.S.A. 91, 7752-7756). Here we use two sets of substrates to examine the probability of replication termination and error-free and error-prone bypass of AAF adducts. The substrates contained site-specific adducts at one of three gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 33 publications
0
27
1
Order By: Relevance
“…Moreover, less fidelity was observed for the lagging-strand replication apparatus when a number of individual template T residues were considered. This difference for PUVA-induced T ⅐ A deletions is consistent with the threefold-less fidelity of the lagging-strand replication apparatus for two nucleotide deletions generated during translesion replication of a site-specific AAF adduct (42). Such PUVA-and AAF-dependent differences in fidelity values are in contrast to the similar average fidelity values of the leadingand lagging-strand replication apparatus for UVB-induced C3T transitions in CPDs (40) and PUVA-induced substitutions (Fig.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Moreover, less fidelity was observed for the lagging-strand replication apparatus when a number of individual template T residues were considered. This difference for PUVA-induced T ⅐ A deletions is consistent with the threefold-less fidelity of the lagging-strand replication apparatus for two nucleotide deletions generated during translesion replication of a site-specific AAF adduct (42). Such PUVA-and AAF-dependent differences in fidelity values are in contrast to the similar average fidelity values of the leadingand lagging-strand replication apparatus for UVB-induced C3T transitions in CPDs (40) and PUVA-induced substitutions (Fig.…”
Section: Discussioncontrasting
confidence: 48%
“…Such differences of mutational spectra may be due to several factors, including excision repair, transcription, and chromatin structures. The level of excision repair activity of the extract used here is low (42), such that most of the adducts introduced by PUVA treatment remain in the DNA and are encountered by the replication fork. Since unincised ICs are expected to block fork progression, we infer that damage-dependent, in vitro, error-prone replication likely involves MAs.…”
Section: Discussionmentioning
confidence: 99%
“…Complete replication past site-specific UV-induced lesions (6,29) or AAF adducts (30,31) in double-stranded DNA carrying the simian virus 40 origin of replication has been observed in HeLa cell extracts, in the presence of T antigen. Recently, using a similar approach, three groups (8,9,28) demonstrated that in contrast to normal cell extracts, extracts from XPV cells were completely (8) or partially (9, 28) deficient in the bypass of a single cis-syn thymine dimer.…”
Section: Discussionmentioning
confidence: 99%
“…AAF adducts at the C8 position of guanine (dGua-C8-AAF) are severe blocks to in vitro DNA synthesis by purified prokaryotic and eukaryotic DNA polymerases (2,21,22). TLS past AAF adducts in both double-stranded (30,31) and forked single-stranded (13) DNA templates has been observed to some extent in cell extracts. This suggests that extracts accurately mimic at least some of the mechanisms that rescue a blocked replication fork in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Psoralen monoadducts (37) and acetylaminofluorene adducts (36) are bypassed with lower fidelity when the adducts are in the lagging-strand template than when they are in the leading-strand template. Furthermore, acetylaminofluorene adducts are much stronger blocks to replication when they are situated in the leading-strand template (40).…”
Section: Discussionmentioning
confidence: 99%